Systematic Detection of Short‐Term Slow Slip Events in Southcentral Alaska - Yutaro Okada; Takuya Nishimura (Geophysical Research Letters)
Abstract Slow slip events (SSEs) are important for the slip budget along a megathrust fault. Although the recurrence of weeks‐long short‐term SSEs (S‐SSEs) in southcentral Alaska has been suggested, a large amount of noise prevented us from detecting discrete events. We applied a systematic detection method to Global Navigation Satellite System data and detected 31 S‐SSEs during the 14‐year analysis period. The events mainly occurred at a depth from 35 to 45 km at a down‐dip extension of the 1964 Alaska earthquake, and the active clusters correlated with the region of the subducting Yakutat microplate. A large cumulative slip of S‐SSEs indicated a significant contribution to stress transfer along the plate interface, and its source area spatially coincided with that of the long‐term SSEs and the afterslip of the 1964 earthquake. Large and recurrent S‐SSEs are key phenomena for understanding interplate slip kinematics in this region.